ANALISIS USAHATANI PORANG PADA USAHATANI ABDUL MUIS DI DESA BERNGAM KECAMATAN BINJAI KOTA, KOTA BINJAI - Hanifa, Naufi Nida; Mastuti, Rini; Supristiwendi, Supristiwendi; Ridha, Ahmad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The porang plant is a plant that has many functions and has a lot of high starch content, especially glucomannan which is widely used by industry. This plant is very easy to grow in Indonesia, one of which is in Bergam Village, Binjai Kota District, Binjai City. This area is very strategic with existing industries in the city of Medan and has the potential for development, especially porang plants. The research objective was to analyze the income, break-even point and R/C ratio of Mr. Abdul Muis' porang (Amorphophallus oncophyllus) farming in Bergam Village, Binjai Kota District, Binjai City. The research used a survey method with a case study approach. The results showed that porang tubers in porang farming were inefficient and not recommended to be continued, while the use of frog/bulbil seeds showed that porang farming was highly recommended to be continued. The R/C ratio value of 2.32 (2.32 > 1) means that Porang Abdul Muis farming in Berngam Village is feasible. To get maximum results farmers are advised to see the right planting season.